Anger Management: Aggression and Punishment in the Provision of Public Goods - Laura Katherine Gee; Xinxin Lyu; Heather Urry (Institute of Labor Economics (IZA), 2017)
The ability to punish free-riders can increase the provision of public goods. However, sometimes the benefit of increased public good provision is outweighed by the costs of punishments. One reason a group may punish to the point that net welfare is reduced is that punishment can express anger about free-riding. If this is the case, then tools that regulate emotions could decrease the use of punishments while keeping welfare high, possibly depending on pre-existing levels of aggression. In this lab experiment, we find that adopting an objective attitude (Objective), through a form of emotion regulation called cognitive reappraisal, decreases the use of punishments and makes a statistically insignificant improvement to both net earnings and self-reported emotions compared to a control condition (Natural). Although the interaction between the emotion regulation treatment and level of aggression is not significant, only low aggression types reduce their punishments; the results are of the same direction but statistically insignificant for high aggression types. Overall, our findings suggest that pairing emotion regulation with punishments can decrease the use of punishments without harming monetary and mental welfare.
Keywords: C72; C91; C92; D7; H41; 330; public goods; punishment; emotions